A soft computing MPPT for PV system based on cuckoo search algorithm - Ahmed, J. (2013)
This paper presents a novel approach to determine the maximum power point (MPP) in Photovoltaic (PV) System using the Cuckoo Search (CS) algorithm. In CS, three samples of voltage are generated randomly over the span of the PV voltage. Based on the Le'vy distribution, the voltage samples are directed towards the best solution and on the basis of power comparison, the best position is found. The algorithm is simulated using MATLAB and compared to the conventional P&O method. It exhibits very fast convergence with zero steady state oscillation. In addition, it tracks the MPP perfectly when PV system is subjected to rapid changes of atmospheric condition.